Increasing Teacher Work Discipline through the Leadership of the School Principal - Khofifah, Lutfi; Patimah, Siti; Kausar, Shakila; Fradito, Aditia (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
This article aims to obtain information and find out the efforts of the madrasa head in improving teacher work discipline. The research method used is descriptive qualitative with the type of field research (field research). Data collection techniques namely observation, interviews, and documentation. The data sources in this study used primary data, namely data sources collected directly from informants, namely the head of the madrasah, deputy head of curriculum, and educators. while secondary data sources are documentation data and other supporting data obtained from madrasas. Data validity was tested by source triangulation and technique triangulation. Data analysis in this study used data reduction, data presentation, and conclusions. The results in this study indicate that: the efforts of the madrasa head to improve the work discipline of teachers in Madrasah Aliyah Mathlaul Anwar, Tanggamus Regency, include: 1) implementing supervision of the rules that have been made by the teacher at work, 2) applying discipline to teachers strictly in imposing sanctions, 3) Increasing teacher work discipline in class attendance, 4) Providing motivation and good examples to teachers in enforcing work discipline, 5) Providing incentives to teachers who have high work discipline in schools, 6) Efforts to increase teacher discipline by the teacher himself.